PH responsive platinum-coated single-walled carbon nanotube optical sensor with internal reference. (30th October 2021) - Shoghi, Fatemeh; Mal, Suraj; Tie, Monique; Badia, Antonella; Martel, Richard
Abstract: Conventional pH meters perform measurements using a two-electrode scheme that consists of a glass electrode (pH) and a reference electrode whose known electrochemical potential is insensitive to pH. This conventional scheme is, however, poorly adapted for remote sensing and in-situ monitoring due to technical difficulties related to making electrical contacts and the stability of the electrodes. By using the highly sensitive Raman response of metallic Single-Walled Carbon Nanotubes (SWCNTs), we devised a pH responsive optical probe comprised of SWCNTs in contact with a platinum redox couple, here referred to as Pt-SWCNTs. When placed in a buffer solution, the Pt-SWCNT probe shows a strong Raman shift of the G-band as a function of pH, which is ascribed to charge transfer doping of the SWCNT reference electrode. Referenced potential measurements are demonstrated along with the accurate monitoring of pH in solutions of different ionic strengths. Controlled experiments at constant ionic strength show precise pH measurements across the full range between 1 and 12 with a best accuracy of ±500 mpH units. This work demonstrates for the first time an optical pH sensing scheme that is analogous to a conventional pH sensor equipped with a built-in internal reference. Graphical abstract: An electrode-less pH nanoprobe made of Single-Walled Carbon Nanotubes (SWCNTs) placed in direct contact with the Pt/PtO redox system is shown to accurately monitor solution pH between 1 and 12. The detection is based on the nondestructive Raman response of metallic nanotubes, which monitors charge transfer doping between the Pt∖PtO redox couple and the nanotubes, ensuring proper reference of the chemical potential. Image 1